Peran Teknik Pencucian dalam Menekan Kontaminasi Kuman di Kantin Kampus Universitas Mulawarman - Ningsih, Riyan; Khasanah, Uswatun (Jurnal Skala Kesehatan, 2026)
Food safety is an important aspect of food provision in higher education environments. This study aims to analyze the relationship between dishwashing techniques and the level of microbial contamination in the University of Mulawarman cafeteria. This research uses a cross-sectional design with observation and laboratory examination of 25 samples of eating utensils. Analysis was performed using Spearman correlation test. The results indicate a significant relationship between washing techniques and the number of microbes (ρ = 0.000), while the sanitation facilities for washing were not significantly related (ρ = 0.596). These findings emphasize the importance of applying proper washing techniques to reduce the levels of microbial contamination. Education for food handlers and improvement of washing facilities are strongly recommended to ensure food safety in campus environments.